#### Answer

3

#### Work Step by Step

From the graph we see that $f(0)=0$ and $g(0)=3$
$g(f(0))=g(0)=3$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

3

From the graph we see that $f(0)=0$ and $g(0)=3$
$g(f(0))=g(0)=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.